Small Proline-Rich Protein 3 Regulates IL-33/ILC2 Axis to Promote Allergic Airway Inflammation - Zhu, Guiping; Cai, Hui; Ye, Ling; Mo, Yuqing; Zhu, Mengchan; Zeng, Yingying; Song, Xixi; Yang, Chengyu; Gao, Xin; Wang, Jian; Jin, Meiling (Frontiers in Immunology, 2022)
Small proline-rich proteins (SPRRs), components of cornified cell envelope precursors, have recently been found to participate in airway diseases, but its role in allergic airway inflammatory remains unknown. Here, we explored the expression of SPRR3 in house dust mite (HDM)-sensitized/challenged mice and attempted to elucidate the regulatory role of SPRR3 in allergic airway inflammation. SPRR3 was identified via bioinformatics analysis of Gene Expression Omnibus (GEO) databases and further confirmed to upregulate in the lungs from HDM-induced mice. Knockdown of SPRR3 via intratracheal route, significantly inhibited eosinophils in bronchoalveolar lavage fluid (BALF) and the expressions of type 2 cytokines (IL-4, IL-5, and IL-13) in BALF and lung tissues. Further, it was confirmed that knockdown of SPRR3 suppressed ILC2 accumulation and the activation of PI3K/AKT/NF-κB pathway in asthmatic lung. In vitro, SPRR3 siRNA could alleviate HDM-induced inflammatory responses in BEAS-2B cells. This study firstly revealed the regulatory role of SPRR3 in allergic airway inflammation, which may become a new therapeutic target for asthma.